2021
DOI: 10.1111/2041-210x.13563
|View full text |Cite
|
Sign up to set email alerts
|

Spot size, distance and emissivity errors in field applications of infrared thermography

Abstract: Infrared thermography is increasingly emerging as an analytical approach within the thermal ecology research community, providing unique and rapid temperature information crucial to understanding how plants and animals exchange heat with their environment. What is difficult to appreciate are the numerous ways in which thermography may still yield inaccurate (i.e. deviation from the ‘correct’ value) information if certain tenets are not followed. In this paper, we examine, demonstrate and discuss these tenets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 31 publications
0
40
1
Order By: Relevance
“…Recent studies have shown that the emissivity and perceived surface temperature of an object can vary according to angle of incidence in an infrared thermographic image (Playà‐Montmany & Tattersall, 2021; Winder et al, 2020). As such, changes in the relative orientation of an object during infrared thermographic imaging may conceal or distort true changes in surface temperature that are driven by biological processes (e.g., vasomotion or contraction of skeletal muscle).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies have shown that the emissivity and perceived surface temperature of an object can vary according to angle of incidence in an infrared thermographic image (Playà‐Montmany & Tattersall, 2021; Winder et al, 2020). As such, changes in the relative orientation of an object during infrared thermographic imaging may conceal or distort true changes in surface temperature that are driven by biological processes (e.g., vasomotion or contraction of skeletal muscle).…”
Section: Methodsmentioning
confidence: 99%
“…Effects of acute stress exposure on surface temperature trends across time differed little from those of our original models at an α of 0.05 (Table S1) despite a reduction in sample size. Next, the yaw of individuals at the time of thermographic image capture was included at a fixed and nonlinear covariate in our models using a thin‐plate regression split with five knots (nonlinear effects reported in Playà‐Montmany & Tattersall, 2021), and both models were subsequently re‐run. In our adjusted models, significant correlations between yaw and surface temperature values were expected to indicate systematic effects of angle of incidence on mean surface temperature values of a specific facial region.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations